Disease, Deformity and Health Terrors in 19th-Century Cartoons: A Cultural History of Science (Theatrum historiae, 2021)
This article analyses the changes that took place in the image of disease during the nineteenth century. Ever since the Enlightenment movement introduced the scientific discourse into popular knowledge in the eighteenth century, a popular scientific culture had developed and been disseminated. The “cultural visualisation” of science via exhibitions, fairs and illustrated publications became even more intense and widespread in the nineteenth century. In this context, satirical images linked to scientific development proliferated. An analysis of this visual language makes it possible for us to learn more about the development of science and its social impact. I analyse the creation and circulation of iconographic sources, with particular emphasis on French and British sources concerning medical and epidemiological subjects. The aim is to understand the visual tradition that shaped these images and its impact on social imaginary. For that purpose, I examine scientific illustrations from the Early Modern to the Modern Era, in order to better understand their iconography and the ways symbolic language concerning epidemic diseases – mainly cholera – spread across Europe in the nineteenth century.
Keywords: Cultural History; Science; Caricature; 19th century; Disease